Perancangan Dashboard Visualisasi Data Key Performance Indicator (KPI) Menggunakan Looker Data Studio Studi Kasus PT. Sicepat Ekspres - Mukhlis Aryanto; Atang Susila (OKTAL : Jurnal Ilmu Komputer dan Sains, 2024)
At PT. Sicepat Ekspres KPI (Key Performance Indicator) system and mechanism have not been formed in a structured and systematic manner, so it is not flexible in conducting data analysis. With the KPI dashboard information find out the performance of each member of the IT Helpdesk team. Based on the Key Performance Indicators (KPI), information on the results of the decision will automatically appear whether members of the IT Helpdesk team have good performance or not. The method used in this study is quantitative because the research is descriptive and focuses on data analysis and data visualization. The results of the complaint tickets handled by the IT helpdesk team from November 6, 2022, to November 13 2022 were 2,477 tickets, and 275 tickets were escalated.  complaints are on the "MAPPING TMS" ticket tag, the most complaint tickets that enter via the WhatsApp channel. The average response time for all agents is 7 minutes 39 seconds. The average resolution time for all agents is 1 hour 16 minutes 24 seconds. a high percentage of tickets was obtained by an agent named Yuda with a CNT of 351 tickets with a percentage of 175.5%. And the total tickets obtained and a low percentage of tickets were obtained by an agent named Alif with CNT of 70 tickets with a percentage of 116.67%. The highest percentage is a positive sentiment as much as 89.8%, then neutral sentiment as much as 8.1%, and the least percentage is a negative sentiment as much as 2.1%, out of a total of 7,939 conversations. The most ticket tags are MAPPING TMS with a positive sentiment of 224 tickets, neutral sentiment of 51 tickets, and negative sentiment of 19 tickets, while the lowest ticket tag is UMS with a positive sentiment of 15 tickets, neutral sentiment of 2 tickets, negative sentiment 2 tickets. The agent name that received the most sentiment from users was named Yuda with a total of 1,099 conversation sentiments which included 987 positive feedback sentiments, 97 conversation neutral feedback sentiments, and 15 negative feedback sentiment conversations. Meanwhile, the agent who received the least sentiment from the user was named Herdian with a total of 150 conversation sentiments which included 132 positive feedback sentiments, 14 neutral feedback sentiments, and 4 negative feedback sentiments. In conclusion, Looker Data Studio can display the Key Performance Indicator (KPI) dashboard online and is easy to share with just the generated link. suggestions for the Looker Data Studio Dashboard KPI program can be developed to display map data or GeoMaps for PT. Sicepat Ekspres branch locations.